TRANSFORMATION OF SWINE PEPSINOGEN INTO SWINE PEPSIN BY CHICKEN PEPSIN - Herriott, Roger M. (The Rockefeller University Press, 1938)
Activation of swine pepsinogen with chicken pepsin results in the formation of swine pepsin. Activation of chicken pepsinogen with swine pepsin results in the formation of chicken pepsin. The structure responsible for the species specificity of the enzyme is therefore present in the inactive precursor.